Molecular Detection of tetA tetB Gene in Escherichia ColiX - Waseem, Nazeeha (International Journal of Pathology, 2022)
Introduction: Gram negative, rod shaped bacterium Escherichia. coli (E. coli )is the most considered microorganism worldwide. The pathogenic variants of E. coli cause serious pediatric diarrhea and other diseases. Antibiotic resistance against E. coli is increasing step by step in emergency clinics and in developing countries like Pakistan. It is dangerous due to frequent use of antibiotics, un hygienic conditions, food and direct contact with animals. Objective: This study was done to assess the tetracycline-resistant genes among isolated E. coli from blood culture received in microbiology laboratory. Materials and methods: study was conducted from January 2020 to January 2021 at the microbiology department of Khyber Medical University. 150 blood samples were inoculated on Blood and MacConkey agar. Identification of E. coli was done by Gram staining and biochemical methods. Molecular confirmation of E. coli was done using specific primers. Antibiotic sensitivity test was performed to identify the tetracycline resistant isolated E. coli phenotypically. Then genotypically, genes conferring tetracycline resistant tet (A & B) were detected using PCR amplification. The PCR amplicons were separated electrophoretically and visualized. Results: In result, out of 150 samples 125 isolated E coli were detected by Gram staining and using MacConkey agar. 120 isolated E. coli were confirmed by API kit biochemically. 114 isolated E. coli were detected genotypically by using uid gene. 57 isolated were resistant against tetracycline and doxycycline. At last, 21 & 39 isolated E. coli were found positive for tetA and tetB genotypically using specific primers. Conclusion: The study of antimicrobial resistant determinants especially the tetracycline resistant genes in blood samples to set guidelines for the control of these pathogenic microbes and for an effective treatment especially in healthcare facilities in Pakistan.